MR contrast enhancement in brainstem and deep cerebral infarction. - Elster, A D (American Journal of Neuroradiology, 1991)
MR imaging with IV administration of gadopentetate dimeglumine was performed in 89 patients with 100 clinically and radiologically documented brainstem or deep cerebral (basal ganglia/internal capsule) infarctions to determine the patterns and time course of contrast enhancement. By location, there were 61 deep cerebral, eight midbrain, 23 pontine, and eight medullary infarctions. The age of the infarctions ranged from 1 day to 3 1/2 years, with 22% of the patients scanned within 4 days and 43% scanned within 2 weeks of clinical ictus. Abnormalities on T2-weighted images were encountered in every case. Mass effect was seen in 10 infarctions, most commonly noted between days 2 and 6, but persisting to day 20 in a single case. Parenchymal contrast enhancement was seen in 43 cases, occurring predominately between days 2 and 80. By postinfarction day 3 only half the strokes enhanced, although all did after day 6. Intravascular enhancement within the vertebral or basilar arteries was noted in five cases; all were brainstem infarctions imaged during the first week following ictus. Meningeal enhancement adjacent to the infarction was not seen in any case. Our results indicate that MR contrast enhancement of brainstem and deep cerebral infarctions typically occurs over a period from about 3 days to 3 months following ictus. Lack of both parenchymal and intravascular enhancement is thus to be expected for several days after a brainstem or deep cerebral infarction.